Nigeria : Technical Assistance Report-Additional Spending Toward Sustainable Development Goals. (IMF Staff Country Reports; Country Report, 2020)
The contents of this report constitute technical advice provided by the staff of the IMF to the authorities of Nigeria in response to their request for technical assistance. Unlocking the potential of a rapidly growing population requires substantial improvements in human and physical capital. Nigeria is Africa's most populous country and its largest economy. Recognizing challenges, Nigeria has embraced the Sustainable Development Goals (SDGs) Agenda. The Economic Recovery and Growth Plan 2017-2020 gives prominence to economic, social and environmental issues. This report assesses additional spending associated with making substantial progress along the SDGs. The report focuses on critical areas of human and physical capital. For each sector, the report documents progress to date, assesses Nigeria relative to peers, highlights challenges, and estimates the spending to make substantial SDG progress. Nigeria has shown gradual improvements in education. A gradual and strategic approach should be considered given the relatively large additional spending.